Development and validation of the Kilifi Epilepsy Beliefs and Attitude Scale. - Mbuba, C; Abubakar, A; Hartley, S; Odermatt, P; Newton, C; Carter, J (2012)
Epilepsy remains misunderstood, particularly in resource poor countries (RPC). We developed and validated a tool to assess beliefs and attitudes about epilepsy among people with epilepsy (PWE) in Kilifi, Kenya. The 50-item scale was developed through a literature review and qualitative study findings, and its reliability and validity were assessed with 673 PWE. A final scale of 34 items had Cronbach's alpha scores for the five subscales: causes of epilepsy (α=0.71); biomedical treatment of epilepsy (α=0.70); cultural treatment of epilepsy (α=0.75); risk and safety concerns about epilepsy (α=0.56); and negative attitudes about epilepsy (α=0.76) and entire scale (α=0.70). Test-retest reliability was acceptable for all the subscales. The Kilifi Epilepsy Beliefs and Attitude Scale is a reliable and valid tool that measures beliefs and attitudes about epilepsy. It may be useful in other RPC or as a tool to assess the effectiveness of interventions to improve knowledge, beliefs, and attitudes about epilepsy.